Gamblers and Dreamers: Women, Men, and Community in the Klondike - Perry, Adele (Labour / Le Travail, 2002)
"The article reviews the book, "
Keywords: Business And Economics–Labor And Industrial Relations; Gold rushes (History); History; History–History of North And South America; Working class